P85 Cognitive symptoms in chronic hepatitis C infection are associated with impaired cognitive test performance but are unrelated to peripheral markers of cellular immune activation. (16th November 2010) - Gess, M; Forton, D
Abstract : Introduction: Patients with hepatitis C virus (HCV) infection frequently complain of "brain fog" and impaired cognitive performance is well described in some patients. A direct virological effect of HCV on the CNS and a central effect of peripheral inflammation have both been hypothesised as mechanisms. Aim: We aimed to determine whether cognitive symptoms are associated with markers of peripheral immune activation and objectively measured cognitive impairment. Method: 53 HCV patients with mild liver disease and 19 healthy controls, matched for age, sex, education and ethnicity, underwent computer-based cognitive testing (United BioSource, UK). The Medical Outcomes Survey Cognitive Function Scale (MOSCog) was used to assess cognitive symptoms. The Fatigue Impact Scale (FIS) and Beck Depression Inventory (BDI) were also employed. Serum neopterin was measured by ELISA, beta-2-microglobulin by nephelometric assay. Results: 19 (36%) HCV patients had MOSCog<75 and formed the symptomatic group and were compared to asymptomatic patients and healthy controls using ANOVA/Kruskal–Wallis tests as appropriate. Symptomatic HCV patients demonstrated significantly worse performance on memory (p=0.013) and attention tests (p=0.008) compared to asymptomatic patients and controls. Neopterin and beta-2-microglobulin levels were higher in HCV patients as a whole (p=0.002) but there were no significant differences between symptomatic and asymptomatic cases. In addition there were no differences in age, gender, ethnicity, education, alcohol intake, history of injection drug use, viral load, genotype and ALT between groups. Symptomatic patients reported worse scores on the BDI and FIS compared to asymptomatic patients (p<0.001) but there were no associations with neopterin and beta-2-microglobulin levels. Conclusion: In summary, important cognitive symptoms in over 1/3 of patients were associated with impaired performance on objective cognitive testing but were unrelated to markers of immune activation. It is unclear whether depression is a primary cause or occurs together with impaired cognition as a result of a direct effect of HCV on the brain.